Gilles Deleuze's time machine - Rodowick, David Norman (Post-contemporary interventions., 1997)
Placing Deleuze's two books on cinema - The Movement-Image and The Time-Image - in the context of French cultural theory of the 1960s and 1970s, Rodowick examines the logic of Deleuze's theories and their relationship to his influential philosophy of difference. Rodowick illuminates the connections between Deleuze's writings on visual and scientific texts and describes the formal logic of his theory of images and signs. Revealing how Deleuzian views on film speak to the broader network of philosophical problems addressed in Deleuze's other books - including his influential work with Felix Guattari - Rodowick shows not only how Deleuze modifies the dominant traditions of film theory, but also how the study of cinema is central to the project of modern philosophy.